Effects of Supplementing Broiler Diets Low in Crude Protein with Essential and Nonessential Amino Acids - Waldroup, P.W.; Jiang, Q.; Fritts, C.A. (International Journal of Poultry Science, 2005)
A study was conducted to evaluate the effects of adding all essential amino acids (EAA) equal to that of higher CP diets or a mixture of nonessential amino acids (NEAA) to low CP diets on the live performance of broilers during the period of 0 to 21 d. A series of experimental diets comprised primarily of corn and soybean meal were formulated to contain 3,200 ME kcal/kg. Five primary diets were formulated to contain 16, 18, 20, 22, and 24% CP. Requirement levels for EAA (110% of NRC, 1994) were accomplished when necessary by adding crystalline amino acids. In each of these dietary series, diets with 16, 18, and 20% CP were supplemented with additional EAA (Trp, Ile, His, Val, Leu, Arg, Gly and Phe) to bring the content of all these EAA to a level equal to that of the 22% CP diet. Additional diets in each series with 16, 18, and 20% CP were supplemented with a mixture of NEAA (equal parts of Ala, Glu, and Glu-NH2) to provide levels of nitrogen equivalent to that provided by the EAA supplementation in the previous diets. Each of the treatments was fed to 12 replicate pens of 5 male chicks of a commercial broiler strain. The reduction of CP level in the starter diets had a significant influence on the live performance. Decreasing CP levels lower than 22% significantly decreased BW gain and increased the feed conversion ratio (FCR). Adding the EAA or NEAA mixtures to the low CP diets significantly improved the performance but did not completely overcome the adverse effects of the low CP diets.